2023
DOI: 10.1177/03331024231177649
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three calcitonin gene-related peptide monoclonal antibodies for migraine: A 12-month, single-center, observational real-world study in Japan

Abstract: Background Real-world data on the effectiveness of calcitonin gene-related peptide monoclonal antibodies (CGRP mAbs) in migraine patients are needed. Methods We performed a single-center, real-world study with an observation period of up to 12 months (mean 7.5 ± 3.4 months) after CGRP mAb administration. A total of 228 Japanese patients with episodic or chronic migraine (age, 45.9 ± 13.2 years; 184F; 45 erenumab; 60 galcanezumab; 123 fremanezumab) who were treated with CGRP mAbs for at least three months were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…Similar results were found in a single-center Japanese real-life study, where no difference in monthly reduction in migraine days over 12 months was found between three CGRP mAbs [22]. Another study of 152 patients compared anti-CGRP mAbs that target the CGRP itself (68 patients; 49 galcanezumab, 19 fremanezumab) to erenumab (84 patients), which targets the CGRP receptor.…”
Section: Discussionsupporting
confidence: 72%
“…Similar results were found in a single-center Japanese real-life study, where no difference in monthly reduction in migraine days over 12 months was found between three CGRP mAbs [22]. Another study of 152 patients compared anti-CGRP mAbs that target the CGRP itself (68 patients; 49 galcanezumab, 19 fremanezumab) to erenumab (84 patients), which targets the CGRP receptor.…”
Section: Discussionsupporting
confidence: 72%
“…With more patients, the results with erenumab would also have been statistically significant. The comparison of efficacy in reducing MMDs among CGRP mAbs is a clinically relevant topic, which should be explored with a much larger population [ 25 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, age, disease duration, baseline MMDs, and baseline HIT-6 were not relevant to 50% RR at V3. Although previous studies found these clinical parameters to be predictors of clinical efficacy, it should be pointed out that there are clear discrepancies among such data in terms of age [ 24 , 31 , 46 ] and baseline MMDs [ 25 , 46 , 47 ]. Hence, there is the possibility that the effectiveness of these parameters as therapeutic predictors is influenced by the difference in study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В японское исследование K. Suzuki и соавт. [19] вошли 228 пациентов, 123 из них получали фреманезумаб, остальные -эренумаб или галканезумаб. Уменьшение числа дней с мигренью в месяц более чем на 50% на 3, 6 и 12-м месяцах лечения составило 48,2; 61,0 и 73,7% соответственно.…”
unclassified